2018
DOI: 10.1364/ol.43.002877
|View full text |Cite
|
Sign up to set email alerts
|

Highly standardized multicolor femtosecond fiber system for selective microphotomanipulation of deoxyribonucleic acid and chromatin

Abstract: We present a three-color femtosecond Er/Yb:fiber laser enabling highly specific and standardized nonlinear optical manipulation of live cells. The system simultaneously provides bandwidth-limited 80-fs pulses with identical intensity envelope centered at wavelengths of 515, 775, and 1035 nm in the focus of a confocal microscope. We achieve this goal by combining high-order dispersion control via, for example, chirped fiber Bragg gratings with proper bandwidth management in each nonlinear conversion step. Wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Twenty-four to forty hours after transfection, medium was replaced by phenolred-free medium for microscopic analysis. Microirradiation and subsequent time-lapse imaging was performed using an inverted laser-scanning microscope (Zeiss LSM700) equipped with a multi-color femtosecond fiber laser setup ( 66 ). In-situ bandwidth-limited optical pulses with a center wavelength of 1035 nm were focused onto the sample using a 63× oil immersion objective lens (N.A.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four to forty hours after transfection, medium was replaced by phenolred-free medium for microscopic analysis. Microirradiation and subsequent time-lapse imaging was performed using an inverted laser-scanning microscope (Zeiss LSM700) equipped with a multi-color femtosecond fiber laser setup ( 66 ). In-situ bandwidth-limited optical pulses with a center wavelength of 1035 nm were focused onto the sample using a 63× oil immersion objective lens (N.A.…”
Section: Methodsmentioning
confidence: 99%
“…For microscopic analysis, cell culture medium was replaced by phenolred-free medium 24 to 40 h after transfection. A Zeiss LSM700 inverted laser-scanning microscope, equipped with a multi-color femtosecond fiber laser setup was employed for microirradiation and following time-lapse imaging (Schmalz et al 2018 ). In situ bandwidth-limited optical pulses (center wavelength 1035 nm) were focused onto the sample with a 63 × oil immersion objective lens (N.A.…”
Section: Aterial and Methodsmentioning
confidence: 99%
“…Another interesting example of the potential of LS for DDR study has been recently reported. In this case the authors employed lasers with three different wavelengths (515, 775, or 1035 nm) but exactly the same pulse length (80-81 fs) (Schmalz et al, 2018). Under conditions of similar average power, different alterations of the chromatin were observed in the irradiated cells.…”
Section: Dna Damage Response and Nuclear Perturbationmentioning
confidence: 99%
“…Therefore, by judiciously choosing the laser parameters (wavelength, pulse duration, power, etc.) it is possible to carry out relevant research on redox cell modulation with OT-like setups ( Westberg et al, 2016 ; Linz et al, 2016 ; Schmalz et al, 2018 ; Gomez-Godinez et al, 2020 ).…”
Section: Perspectivesmentioning
confidence: 99%